Multi-Channel Radio-Over-Fiber Communication Systems Through Modulation Instability Phenomenon - Rasul Azizpour; Hassan Zakeri; Gholamreza Moradi; Mohammad Alibakhshikenari; Francisco Falcone; BO Liu; Tayeb A. Dendini; Imko Park; Slawomir Koziel; Ernesto Limiti (IEEE Photonics Journal, 2024)
Recent advancements in Radio-over-Fiber (RoF) technology have positioned it as a promising solution for high-capacity wireless communications. This paper explores novel applications of RoF systems in enhancing phased array antenna (PAA) performance for multi-channel wireless communication applications through the modulation instability (MI) phenomenon. Utilizing fibers experiencing MI with varying group velocity dispersions ( $\beta _{2}$ ) of −20, −11.3, −3.2, and −2 $\text{ps}^{2}/\text{km}$ , the RoF system achieves operational flexibility across distinct central frequencies of 12, 16, 30, and 38 GHz, respectively. This approach represents a significant advancement in wireless communication technology, leveraging MI gain and an MI-based control system architecture to enhance performance across diverse frequency bands. The study investigates the impact of MI on modulation efficiency, presenting experimental results validating the feasibility and effectiveness of the proposed approach. The maximum MI gain by employing a 30 km fiber under MI is 18 dB, experimentally. Further optimization, achieved by increasing the fiber length to 45 km and adjusting nonlinear parameters and input power, demonstrates a remarkable MI gain of 38.1 dB. MI-based true time delay (TTD) techniques also address beam squint challenges, enhancing beamforming capabilities. The findings suggest that integrating MI into RoF systems holds excellent potential for improving wireless communication capabilities with reduced costs and space requirements compared to conventional methods. This research contributes to the growing body of knowledge in the field of RoF systems and offers insights into their practical applications in modern wireless communication networks.